SAFE MANAGEMENT OF E-WASTE DISPOSAL TO PREVENT HARMFUL EFFECTS ON HUMAN HEALTH AND THE ENVIRONMENT - Yuliana Yuliana (Poltekkes Kemenkes Yogyakarta, 2022)
Using electronic devices is a common thing nowadays. Moreover, in the COVID-19 pandemic, all activities must be done from home. Learning, working, and leisure activities are done from home by gadgets. Therefore, electronic device demands are getting higher. E-waste disposal must be a concern for all electronic device users. Lack of awareness on proper management for e-waste disposal may cause harmful effects on human health, plants, soils, and the environment. The effects are increasing the risks of cancers, soil, and environmental pollution. This paper aims to describe the safe management of e-commerce-waste disposal to prevent harmful effects on human health and the environment. Databases from Science Direct, PubMed, and Google Scholar were used. The keywords were disposal AND environment AND e-waste AND health AND management. There were 2170 journals at the beginning. After screening by the title, abstract, and full text, there were 35 journals. Inclusion criteria were full text available, review, and research. Exclusion criteria are opinion and commentary. Reverse logistics is a way to dispose of e-waste by increasing the economic value of the waste. Another alternative to e-waste management is making art and craft from e-waste. Conclusion: Reverse logistics must be taught to people to save the planet from the harmful effects of the unwise management of e-waste disposal. Art and craft from e-waste can be done to increase economic value and reduce hazards to health and the environment. Soil assessment of heavy metal concentration surrounding the waste dump area must be done regularly to prevent bioaccumulation.